Pengaruh Citra Merek, Harga, dan Kualitas Produk Terhadap Keputusan Pembelian Iphone (Studi Kasus Pada Mahasiswa di Kota Malang ) - Prasetyo, Yogi Adha; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine the influence of brand image, price and product quality on iPhone purchasing decisions among students in Malang City. The research method used is quantitative with an explanatory research approach. Data was collected through surveys using valid and reliable research instruments. Data analysis was carried out using statistical techniques to test the proposed hypothesis. The research results show that simultaneously, brand image, price and product quality have a positive and significant influence on iPhone purchasing decisions. However, partially, the brand image variable does not have a significant effect on purchasing decisions, while the price variable does not have a significant effect. On the other hand, product quality has a significant influence on iPhone purchasing decisions. This research has important implications for companies in optimizing marketing strategies, especially in strengthening brand image and improving product quality as the main factors influencing consumer purchasing decisions. Positive customer experiences also need to be considered as part of a holistic marketing strategy to increase consumer loyalty. Keywords: Brand Image, Price, Product Quality, Purchase Decisions